Environmental Graphic Design for Ballyson Stationery Store - Vanessa; Ria Sapitri (JURNAL RUPA MATRA, 2022)
The commercial is something that is meant by trade, has high commercial value, and sometimes sacrifices other values ​​such as social, cultural, and so on. The commercial sector always exists in various countries, one of which is Indonesia, where there are already many trading businesses. One example of a trading business in Indonesia is a shop called Ballyson which is located in Batam City which is in the Riau Islands Province. This shop sells a variety of stationery, office supplies, sports, and more. With the sale of various kinds of stationery, this shop does not yet have a sign that can easily distinguish where the location of the goods that the customer is looking for. Therefore, this is where the role of a graphic designer is to identify that this store lacks supporting facilities to provide information on the placement of the merchandise in the stationery shop. The author will focus on the signage area in the hope of facilitating the shopping process for customers. In addition, the author can also act as a wayfinding and interior designer to facilitate the trading process.